Analisa Penggunaan Bahan Bakar Pellet Kayu pada Tungku Biomassa - Rizki Agustian; Yolli Fernanda; Arwizet K; Andre Kurniawan (Jurnal Vokasi Mekanika (VoMek), 2025)
Along with population growth and global industrialization, the level of fossil fuel use continues to increase. If fuel consumption continues to increase without proper maintenance, the fuel oil (BBM) crisis will become an unavoidable problem. Utilizing biomass as a source of energy is profitable because theoretically it does not produce the greenhouse gas CO2 which is detrimental to the environment. However, conventional biomass stoves still face problems related to exhaust emissions and combustion efficiency. This study's objective is to make a biomass stove that can reduce exhaust emissions to increase combustion efficiency, thus supporting the use of environmentally friendly energy. The method usually used is by changing the mass of wood pellets during boiling water into the combustion chamber. The weight ranges between 300 grams, 400 grams, 500 grams, 600 grams and 1400 grams, each according to the capacity of the combustion chamber. The five types of tests aim to determine the extent to which differences in wood pellet mass and biomass stove type have on the combustion process, as well as how long the process takes. The findings of the study show that variations in the mass of wood pellets greatly influence the boiling time of water, with a mass of 300 grams the boiling time has not yet reached the boiling point of the water, with a mass of 400 grams it gets 23 minutes, with a mass of 500 grams it gets 25 minutes, with a mass 600 grams can be obtained in 26 minutes